A Generalized Model of Pricing for Homogeneous Goods under Imperfect Information - Sadanand, Asha; Wilde, Louis (Review of Economic Studies, 1982)
This paper generalizes the model developed in Wilde and Schwartz (1979) to allow downward sloping demand curves and u-shaped average cost curves. It shows that the basic qualitative conclusions of Wilde and Schwartz still hold. Moreover, it shows that the critical proportion of comparison shoppers needed to generate a competitive equilibrium falls as demand becomes more elastic or average costs become more inelastic. Finally, it shows that when imperfect information generates non-competitive outcomes, they are bounded below, in welfare terms, by the monopolistically competitive equilibrium.